Biaya Kebakaran Gambut yang Ditanggung oleh Rumah Tangga Petani di Kecamatan Air Sugihan, Kabupaten Ogan Komering Ilir - Novi Anggraini; Harianto Harianto; Harmini Harmini (Jurnal Ilmu Pertanian Indonesia, 2023)
The purpose of this study is to estimate the costs borne by farming households due to peatland fires. The research location was Air Sugihan District, Ogan Komering Ilir Regency, and 3 villages were selected representing the district i.e., Rengas Abang Village, Nusa Karta Village, and Jadi Mulya Village. Twenty samples of farmer households were taken as respondents. Data collection activities were carried out in August‒September 2021. Data analysis methods used Cost of Illness, Loss of Earnings, Equivalency Analysis, and Loss on Farming. Economic losses due to forest and peatland fires in Air Sugihan District, Ogan Komering Ilir Regency amounted to IDR773.338.080 with 1.91% of medical expenses, 0.27% of additional cost of drinking water, 41.91% of increase in farming costs, and losses of farmer income by 55.91%, or IDR557,160/week/farmer household with a total of 1,388 households. The costs paid by farming households in Air Sugihan District, Ogan Komering Ilir Regency due to peatland fires, increased substantially compared to the cost paid before the fire was occurred. It is concluded that in minimizing the impact of forest and peatland fires it is necessary to carry out interventions so that similar incidents do not recur in the future. Keywords: cost, farmers, impact of fire, peatland fires